The Asymmetric Relationship between Corruption, Political Stability and Economic Growth: Evidence from India - Dr. Meenakshi P.G,; Dr. Gupta Verma, (Al-Qanṭara, 2022)
There are studies available that study the influence of corruption on economic growth, but no existing literature studies the asymmetric relationship in context to India. In this study, we try to fill the gap in the literature by studying the symmetric and asymmetric association between corruption, political stability and economic growth in India where gross fixed capital formation and final consumption expenditure are considered additional variables. Further, we employ panel non-linear autoregressive distributed lag model from 1996–2018. In the long run, the non-linear estimation results confirm an asymmetric relationship while all variables show the asymmetric relationship in the short run. The research found that there is positive and significant link. Keywords- economic growth, corruption, asymmetric, India.